A direct synthesis of carboxylic acids via platinum-catalysed hydroxycarbonylation of olefins. Issue 8 (25th January 2021) - Schneider, Carolin; Franke, Robert; Jackstell, Ralf; Beller, Matthias
Abstract : A selective platinum-catalysed hydroxycarbonylation of aliphatic olefins has been achieved. Abstract : The platinum-catalysed hydroxycarbonylation of olefins is reported for the first time. Using a combination of PtCl2 /2, 2′-bis( tert -butyl(pyridin-2-yl)phosphanyl)-1, 1′-binaphthalene (Neolephos) in the presence of sulfuric acid [0.6 M] in acetic acid selective carbonylation of terminal aliphatic olefins proceeds to good yields and selectivities to the corresponding carboxylic acids. Comparing the reactivity of different butenes (iso- and n -butenes), the terminal olefin can be selectively carbonylated.